2015
DOI: 10.1111/psyp.12565
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural white matter changes mediate age‐related cognitive decline on the Montreal Cognitive Assessment (MoCA)

Abstract: Although the relationship between aging and cognitive decline is well established, there is substantial individual variability in the degree of cognitive decline in older adults. The present study investigates whether variability in cognitive performance in community-dwelling older adults is related to the presence of whole brain or tract-specific changes in white matter microstructure. Specifically, we examine whether age-related decline in performance on the Montreal Cognitive Assessment (MoCA), a cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 84 publications
(106 reference statements)
5
20
0
Order By: Relevance
“…For instance, reduced efficiency of top‐down control mechanisms (e.g., CRUNCH, Reuter‐Lorenz & Cappell, ) can incorporate both reduced structural/functional connectivity and increased frontal and bilateral cortical recruitment at lower levels of cognitive load in older adults (see Schneider‐Garces et al, ). Importantly, declines in prefrontal cortex tissue and cognitive control performance in older adults are increasingly shown to vary with the presence of modifiable cardiovascular and cerebrovascular factors (e.g., Chiarelli et al, ; Fabiani, Gordon et al, ; Fabiani, Low et al, ; Jolly et al, ; Tan et al, ; Zimmerman et al, ) and to be, at least partly, mitigated by cardiorespiratory fitness (Fletcher et al, ; Gordon et al, ; Kramer et al, ). Exercise intervention programs appear to stave off, if not reverse, some of the declines in cognitive control found in older adults (Bherer, Erickson, & Liu‐Ambrose, ; Colcombe & Kramer, ; Gajewski & Falkenstein, ; Heyn, Abreu, & Ottenbacher, ; Smith et al, ) and more recently in inactive children (Chaddock et al, ; Hillman, Erickson, & Kramer, ).…”
Section: Brain Mechanisms In Support Of Cognitive Controlmentioning
confidence: 99%
“…For instance, reduced efficiency of top‐down control mechanisms (e.g., CRUNCH, Reuter‐Lorenz & Cappell, ) can incorporate both reduced structural/functional connectivity and increased frontal and bilateral cortical recruitment at lower levels of cognitive load in older adults (see Schneider‐Garces et al, ). Importantly, declines in prefrontal cortex tissue and cognitive control performance in older adults are increasingly shown to vary with the presence of modifiable cardiovascular and cerebrovascular factors (e.g., Chiarelli et al, ; Fabiani, Gordon et al, ; Fabiani, Low et al, ; Jolly et al, ; Tan et al, ; Zimmerman et al, ) and to be, at least partly, mitigated by cardiorespiratory fitness (Fletcher et al, ; Gordon et al, ; Kramer et al, ). Exercise intervention programs appear to stave off, if not reverse, some of the declines in cognitive control found in older adults (Bherer, Erickson, & Liu‐Ambrose, ; Colcombe & Kramer, ; Gajewski & Falkenstein, ; Heyn, Abreu, & Ottenbacher, ; Smith et al, ) and more recently in inactive children (Chaddock et al, ; Hillman, Erickson, & Kramer, ).…”
Section: Brain Mechanisms In Support Of Cognitive Controlmentioning
confidence: 99%
“…The few studies do report RaD have found it to be more sensitive than other DTI measures to cognitive performance in older adults [Borghesani et al, ; Haász et al, ]. Jolly et al [] showed that, compared with cortical atrophy, white matter hyperintensities and other DTI measures, RaD was the strongest predictor of scores on the Montreal Cognitive Assessment [MoCA; Nasreddine et al, ]. Moreover, whole brain RaD was a better predictor of MoCA scores than RaD in any one of the 18 white matter tracts extracted based on the probabilistic white matter tract atlas from the John Hopkins University [Hua et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, whole brain RaD was a better predictor of MoCA scores than RaD in any one of the 18 white matter tracts extracted based on the probabilistic white matter tract atlas from the John Hopkins University [Hua et al, ]. In fact, the relationship between MoCA scores and RaD in each individual white matter tract did not remain significant when controlling for whole brain RaD [Jolly et al, ]. This is not surprising as the MoCA is a global cognitive screening tool that assesses memory, attention and executive functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that vascular risk factors may influence brain anatomy and cognitive function even in the absence of stroke or Alzheimer’s disease. For instance, Raz and colleagues (2007) showed an association between vascular risk factors, smaller prefrontal volumes, and lower scores on tests of fluid intelligence (see also Jolly et al, 2016; 2017). Similarly, a meta-analysis examining the effects of peripheral blood pressure reported that 26 of the 28 studies included showed an association between hypertension and volumetric reductions in the brain, with particularly strong effects in the frontal and temporal lobes (Beauchet et al, 2013).…”
Section: Introductionmentioning
confidence: 97%